2019
DOI: 10.3133/sir20185150
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of base flow on ungaged, periodically measured streams in small watersheds in western Pennsylvania

Abstract: For an overview of USGS information products, including maps, imagery, and publications, visit https://store.usgs.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Our findings indicated that the trend of DACP reversed due to open cut mining and only went back again when it was also affected by underground mining (Figure ). The results confirmed that the increase in baseflow was caused by open cut mining, which is similar to increased baseflow durations in mined catchments in the previous studies (Hittle & Risser, ). The increased baseflow is likely caused by the loss of evapotranspiration of vegetation removal and the change in overland flow and infiltration associated with landscape changes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings indicated that the trend of DACP reversed due to open cut mining and only went back again when it was also affected by underground mining (Figure ). The results confirmed that the increase in baseflow was caused by open cut mining, which is similar to increased baseflow durations in mined catchments in the previous studies (Hittle & Risser, ). The increased baseflow is likely caused by the loss of evapotranspiration of vegetation removal and the change in overland flow and infiltration associated with landscape changes.…”
Section: Discussionsupporting
confidence: 90%
“…Dewatering activities to sustain the underground mining operations has drastically deceased groundwater level, which affected the recharge between groundwater and baseflow, resulting in Water Resources Research a reduction in baseflow and zero streamflow when precipitation is minimal (Abiye et al, 2018). Subsidence and large voids due to underground mining activities may enhance the effects of increasing hydraulic conductivity and the capacity of the subsurface water storage, which may result in the reduction of baseflows (Booth, 2002(Booth, , 2007Hittle & Risser, 2019). More research is needed to determine if these response mechanisms are consistent across different regions and when or how they vary with mining practices.…”
Section: Uncertainties Under the Climate Variabilitymentioning
confidence: 99%
See 1 more Smart Citation